Application of Copper Nanoparticles in Dentistry - Veena Wenqing Xu; Mohammed Zahedul Islam Nizami; Iris Xiaoxue Yin; Ollie Yiru Yu; Christie Ying Kei Lung; Chun Hung Chu (Nanomaterials, 2022)
Nanoparticles based on metal and metallic oxides have become a novel trend for dental applications. Metal nanoparticles are commonly used in dentistry for their exclusive shape-dependent properties, including their variable nano-sizes and forms, unique distribution, and large surface-area-to-volume ratio. These properties enhance the bio-physio-chemical functionalization, antimicrobial activity, and biocompatibility of the nanoparticles. Copper is an earth-abundant inexpensive metal, and its nanoparticle synthesis is cost effective. Copper nanoparticles readily intermix and bind with other metals, ceramics, and polymers, and they exhibit physiochemical stability in the compounds. Hence, copper nanoparticles are among the commonly used metal nanoparticles in dentistry. Copper nanoparticles have been used to enhance the physical and chemical properties of various dental materials, such as dental amalgam, restorative cements, adhesives, resins, endodontic-irrigation solutions, obturation materials, dental implants, and orthodontic archwires and brackets. The objective of this review is to provide an overview of copper nanoparticles and their applications in dentistry.